2016
DOI: 10.1038/srep33454
|View full text |Cite
|
Sign up to set email alerts
|

Micro-bubble emission boiling with the cavitation bubble blow pit

Abstract: The miniaturization boiling (micro-bubble emission boiling [MEB]) phenomenon, with a high heat removal capacity that contributes considerably to the cooling of the divertor of the nuclear fusion reactor, was discovered in the early 1980s. Extensive research on MEB has been performed since its discovery. However, the progress of the application has been delayed because the generation mechanism of MEB remains unclear. Reasons for this lack of clarity include the complexity of the phenomenon itself and the high-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Zeigarnik et al analyzed the components of the microbubbles from collapsed vapor films in MEB and deemed that they were the mixture of vapor and noncondensable gases. Recently, Inada et al experimentally studied boiling of a liquid droplet on a small heating surface to clarify the process of subcooled liquid rushing to the heating surface. They found that the microbubbles were resulted from cavitation caused by collapse of vapor bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Zeigarnik et al analyzed the components of the microbubbles from collapsed vapor films in MEB and deemed that they were the mixture of vapor and noncondensable gases. Recently, Inada et al experimentally studied boiling of a liquid droplet on a small heating surface to clarify the process of subcooled liquid rushing to the heating surface. They found that the microbubbles were resulted from cavitation caused by collapse of vapor bubbles.…”
Section: Introductionmentioning
confidence: 99%
“…The oscillatory flow induced by the non-uniform bubble oscillations in MEB promotes the delivery of heat from the vapour bubble to the cold bulk, allowing the local subcooling near the heating surface to be maintained. This may help to stabilize the heat transfer in MEB since the occurrence of MEB is inhibited after subcooling decreases to below 20 K (Suzuki et al 2002;Ando et al 2016;Inada et al 2016;Tang et al 2017).…”
Section: Effect Of the Boiling Mode On Bubble-induced Flowmentioning
confidence: 99%
“…In 1981, a boiling phenomenon called microbubble emission boiling (MEB) was observed in the transition boiling region under highly subcooled conditions by Inada et al (1981). MEB has been proved to be able to achieve a heat flux several or even ten times higher than CHF (Suzuki, Saitoh & Matsumoto 2002;Ueno, Hattori & Hosoya 2011;Ando et al 2016;Inada et al 2016;Tang et al 2017;Sinha et al 2020) and is a potential cooling method for devices characterized by very large heat release.…”
Section: Introductionmentioning
confidence: 99%
“…The drop test experiment and its results is important in thermal engineering application such as power plant [9]- [10], material manufacturing process [11], thermal energy and cooling studies [12]- [14], quenching and spray cooling studies [15]- [17] and many others. Drop impact researcher such as Moita and Moreira [18], Illias et al [19]- [26], Mitsutake et al [27]- [28], Inada et al [29]- [30] and many other uses a single drop test in their experimental work. Drop test experiment can be used to study the behavior of impacting droplets, evaporation characteristic, vapor film generation, heat flux analysis and many others.…”
Section: Introductionmentioning
confidence: 99%